Can environmental regulation promote urban innovation in the underdeveloped coastal regions of western China?. (November 2021) - Nie, Xin; Wu, Jianxian; Zhang, Wei; Zhang, Jun; Wang, Wenhuan; Wang, Yinghui; Luo, Yaping; Wang, Han
Abstract: The Porter hypothesis states that environmental regulation can promote innovation. China faces serious environmental pressure and demand for innovation, and has a goal of becoming one of the most innovative countries by 2035. Due to China's vast territory and uneven development, realizing this goal will depend on both the economically developed coastal cities in the east, and the influence of underdeveloped coastal cities in the west. Given this context, this study investigates the causal relationship between environmental regulation and innovation in underdeveloped coastal cities, using the synthetic control method. The empirical analysis results show that environmental regulation has promoted innovation in underdeveloped coastal regions in western China, and the Porter hypothesis is verified to apply in the underdeveloped areas of developing countries. The research indicates there are certain differences among underdeveloped coastal cities; as such, local conditions should drive specific environmental regulation policies, whether they are in China or other developing countries. Specifically in China, the Guangxi government should adopt strict marine environmental regulation policies to force Fangchenggang industrial enterprises to make changes towards cleaner and more sustainable production, and should continue to promote innovative development of the city. Evidence from the world's largest developing country indicates that environmental regulation and innovation can provide a win-win in underdeveloped areas, in contrast to the view of environmental Kuznets curve. Highlights: Environmental regulation can promote innovation in underdeveloped coastal city. Porter hypothesis is established in underdeveloped areas of developing countries. Local conditions should drive specific environmental regulation policies. Environmental regulation and innovation can be win-win in underdeveloped areas.